2010
DOI: 10.1007/s00436-010-1976-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of heterophyiosis in Tilapia fish and humans in Northern Egypt

Abstract: A total of 100 Tilapia fish samples were collected from brackish water (n = 50) and fresh water (n = 50) resources, Northern Egypt, and examined for heterophyid encysted metacercariae (EMC) during the period from August 2007 to July 2008. The overall prevalence of infection was 32%; 22% for brackish water fish and 42% for fresh water fish. Significant differences in parasite occurrence among body regions were found, with muscles of the tail and caudal third being highly affected (93.4%) followed by middle thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 16 publications
0
16
1
Order By: Relevance
“…However, many other species of fish also entered the fishponds from the surrounding natural environment via drainage of water from irrigation canals. These species include C. striata, L. bleekeri, and T. trichopterus, which can serve as second intermediate host of the trematodes C. caninus and H. yokogawai (Lobna et al, 2010). In this study, we found only C. caninus infection in L. bleekeri.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, many other species of fish also entered the fishponds from the surrounding natural environment via drainage of water from irrigation canals. These species include C. striata, L. bleekeri, and T. trichopterus, which can serve as second intermediate host of the trematodes C. caninus and H. yokogawai (Lobna et al, 2010). In this study, we found only C. caninus infection in L. bleekeri.…”
Section: Discussionmentioning
confidence: 86%
“…Tilapia was reported to infect with Haplorchis sp. (Lobna et al, 2010), but there have been no surveys of the parasite in wild or cultivated tilapia in Thailand.…”
Section: Discussionmentioning
confidence: 96%
“…Heterophyid infections occur in brackish and fresh water fish in northern Egypt, where the parasites are indigenous [66]. The highest intensity of infection has been detected among fishermen (33.8%) [67] and local residents in northern Egypt (13.3%) [68]. The overall prevalence of heterophyid infection of fish has been reported to be 32%, that is, 22% for brackish water fish and 42% for fresh water fish [68].…”
Section: Prevalence Of Parasitic Zoonoses Among Humans and Animals Inmentioning
confidence: 99%
“…The highest intensity of infection has been detected among fishermen (33.8%) [67] and local residents in northern Egypt (13.3%) [68]. The overall prevalence of heterophyid infection of fish has been reported to be 32%, that is, 22% for brackish water fish and 42% for fresh water fish [68]. In the Ismailia Governorate, the prevalence of heterophyid metacercaria in fresh water fish was found to be 95.4% [69].…”
Section: Prevalence Of Parasitic Zoonoses Among Humans and Animals Inmentioning
confidence: 99%
See 1 more Smart Citation